Análise espaço-temporal do escoamento fluvial nas bacias hidrográficas dos rios Aguapeí e Peixe, Oeste Paulista, Brasil - Andrade, Lucinete, Ferreira [UNESP] (2014)
Regarding the tools water management, the articulation to impose the policies such as charging for the use of water resources, in addition to grants use rights in Aguapeí and Peixe River basin, this research aims to perform spatio-temporal analysis, based on geographic and hydrological knowledge. The research area is incorporated at the same Watershed Committee (Committee of Aguapeí and Peixe River Basin) on West of state of São Paulo. Based on the hypothesis of hydrological periods of rivers regimen (which is a variation in the magnitude of the flow over time) of data collected and the theoretical and methodological structure, this research presents a hydrological zoning maps in the boundaries of SIGRH and CBH-AP area as a product from the correlations among morphometric and hydrologic data along the different hydrological periods observed. The results indicate the differences in the spatio-temporal water availability. At first period (1948-1972) the specific flow average magnitude have been the lowest of the series; At second period (1972-1984) have been those with the highest magnitude, greatest than the third period (1985-2000), when the magnitude may be considered intermediary